Sentiment Analysis of Literature on Sharia Credit Card - Irni Nuraini (Fara'id and Wealth Management, 2022)
This study was carried out to examine the Islamic credit card within the context of Islamic economics in terms of scientific research produced in response to the introduction of Islamic credit cards. Descriptive bibliometric statistical analysis and sentiment analysis are applied to secondary data in the form of 134 papers published over the last nine years and then processed with VOSViewer and SentiStrength. The results demonstrated that bibliometric mapping is divided into two clusters, with cluster 1 containing 33 keywords and cluster 2 containing 26. The results of sentiment analysis of the literature indicate 34% positive sentiment, 25% negative sentiment, 41% neutral sentiment, and 0% high negative and high positive sentiment.